Metagenomic and isotopic signatures of the Amazon River plume into the southern red snapper fish (Lutjanus purpureus) - Nogueira, Luciane de C.; Asp, Nils E.; Rezende, Carlos E.; Sousa, Rodrigo Petry C.; Barros, Breno; Paixão, Raphael; Gatts, Pedro V.; Thompson, Cristiane C.; Francini-Filho, Ronaldo B.; Vallinoto, Marcelo; Thompson, Fabiano L. (Estuarine, coastal and shelf science, 2023)
The Amazon reef system harbors a large proportion of the fish diversity known for the SW Atlantic, including some critical fishery resources, such as the Southern Red Snapper, Lutjanus purpureus, that thrives in the Great Amazon Reef System (GARS). Brazilian exports of L. purpureus result in millions of dollars every year, being socio-economically relevant at northern Brazil. Its capture is largely associated with the GARS. On the other hand, its regional abundance is attributed to the productivity of the area, which is, in turn, the result of the Amazon River plume (ARP). Thus, its trophodynamics is rather complex and important to understand the ARP-GARS linkage. The aim of the present study was to evaluate the trophic ecology of this fish and the possible influences of the nutrients from the ARP. To this end, gut microbiome and stable isotopic profiling of the gut and muscles of L. purpureus were performed. Fish samples were collected at two different stations (S8, S10) at different distances from the coast. The isotopic composition (δ13C and δ15N) of the fish tissues shows the influence of the river plume (particulate and dissolved), suggesting a substantial contribution of continental organic matter to L. purpureus food items. A total of ten 16S rRNA illumina libraries were obtained from the gut contents (546,301 sequences). The presence of picoplanktonic plume microbes (Synechococcus, Cyanobium, SAR324, Blastopirellula, Vibrio) in the gut microbiome of L. purpureus reinforces the influence of the river plume on the diet of this fish. Fluxes from the Amazon Forest and river nutrients which reach the ocean may indirectly contribute to the nutrition of L. purpureus through the food web by fueling its invertebrates and fish preys. •Microbiomes of L. purpureus are largely associated to the Amazon River plume.•Stable isotopes of L. purpureus show a substantial continental organic matter input.•The Amazon River input affects the trophic web in the area even in its higher levels.•Results support the strong trophic linkage of L. purpureus and the reefs (GARS).